THE EFFECT OF MERRY RIANA YOUTUBE CHANNEL ON THE EPISODE “SMARTNESS ALONE IS NOT ENOUGH FOR YOU TO BE SUCCESSFUL” ON STUDENT LEARNING MOTIVATION - Endah Purwitasari; Ardiya Putra Mahardika; Fitri Dwi Lestari (Journal of Digital Media Communication, 2022)
The development of this technology eventually led to a more creative audio-visual era. The era of social media that is increasingly dominant makes the needs of users or internet users meet their information needs and search for information to satisfy these needs, which can be obtained and fulfilled audio and visually through YouTube. Content creators have the opportunity to be able to attract audience segmentation with lots of videos uploaded on their YouTube channel accounts. This study aims to determine how much influence Merry Riana's YouTube channel shows on the episode "smartness alone is not enough for you to be successful" on student learning motivation. The theory used in this research is the cognitive-behavioral theory, where this theory explains the pattern of human behavior. In this theory, individuals tend to form their conceptions which will directly influence their behavior. This study uses quantitative methods by distributing questionnaires to 100 student respondents from Gunadarma University. The analysis technique used is simple linear regression analysis. Respondents are students who have watched Merry Riana's video in the episode "smartness alone is not enough for you to be successful." The results of this study stated that the magnitude of the influence of Merry Riana's YouTube channel on the episode "change difficult to success" on student learning motivation was 56.8%. Based on these results, the hypothesis in this study was accepted with an explanation that there was an influence from Merry Riana's YouTube channel shows on the episode "smartness alone is not enough for you to be successful" on student learning motivation.